Implementasi Manajemen Peserta Didik Di SMK Negeri 1 Siborongborong - Susi Susanti Situmorang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of student management at SMK Negeri 1 Siborongborong, which includes planning, implementation steps, guidance, evaluation, and the student transfer system. Student management is one of the important aspects of school management that functions to organize and provide services to students from the admission process until graduation. Proper management is expected to support the optimal development of students' potential, interests, and talents. This study uses a descriptive qualitative approach with a case study design. Data collection techniques were carried out through observation, interviews, and documentation. The research informants consisted of the principal, vice principal for student affairs, teachers, homeroom teachers, and guidance and counseling teachers. Data analysis was conducted inductively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of student management at SMK Negeri 1 Siborongborong has been carried out systematically and participatively. Planning is conducted through an initial academic year work meeting involving all relevant stakeholders. The planning steps are prepared based on needs analysis and evaluation of previous programs. Student guidance is implemented continuously through an educational and character-building approach. Student evaluation is carried out periodically, covering academic and behavioral aspects. The student transfer system is implemented in accordance with applicable administrative procedures. Overall, student management at the school has been well implemented and supports the improvement of educational quality.